Pemanfaatan Poster Abjad Bergambar Untuk Mengembangkan Kemampuan Bahasa Dan Kognitif AUD - Lailatul Nur Asri; Rachma Hasibuan (Khirani: Jurnal Pendidikan Anak Usia Dini, 2024)
The background to this research includes family planning students (aged 3-4 years) in PAUD who have difficulty re-naming letters that have been introduced. The aim of this research is to improve language skills regarding recognizing letters and cognitive abilities regarding recognizing animal names through illustrated alphabet posters. The method used in this research is descriptive research. The results of this research were several students who achieved very good development in recognizing letters where students were able to independently and help their friends in recognizing letters and at the same time students were able to recognize the names of animals through this poster. The conclusion of this research is that using illustrated alphabet posters can improve language skills in the material recognizing letters and can improve cognitive abilities in the material recognizing animal names. The level of achievement of language and cognitive development has increased. It is proven that illustrated alphabet posters can improve AUD's language and cognitive abilities because the illustrated alphabet posters are used by students to recognize letters and animal names easily and in a fun way.